Unveiling of genetic variability in garlic (Allium sativum L.) genotypes grown in Pakistan - Attique ur Rehman, Malik; Khattak, Sahir Hameed; Inam, Safeena; Rehman, Nazia; Hussain, Muzammil; Ali, Shaukat; Shahid, Muhammad Munir; Khan, Muhammad Ramzan (Journal of Pure and Applied Agriculture, 2023)
Garlic (Allium sativum) is the second most widely cultivated Allium species grown in the world. But lack of development of improved varieties remains a major bottleneck in achieving higher yield. For varietal development programs, insufficiency of existing cultivars and genetic data are the major constraints. In the current study field trials for 3 consecutive years (2018 to 2020) were conducted to evaluate genetic variability among four different garlic genotypes in comparison with two newly developed advance lines. Based on 13 agro-morphological traits, garlic genotypes were evaluated in Randomized Complete Block design (RCBD) with three replications